Prevalence and severity of patient harm in a sample of UK-hospitalised children detected by the Paediatric Trigger Tool. Issue 7 (3rd July 2014) - Chapman, Susan M; Fitzsimons, John; Davey, Nicola; Lachman, Peter
Abstract : The measurement and examination of adverse events (AEs) that occur in children during hospital admissions is essential if we are to prevent, reduce or ameliorate the harm experienced. The UK Paediatric Trigger Tool (UKPTT) is a method of retrospective case note review that measures harm in hospitalised children. Objectives: To examine the harm resulting from the processes of healthcare in hospitalised children from centres providing data to the National Health Service (NHS) Institute UKPTT data portal, to understand the positive predictive values of triggers and to make recommendations for the further development of the trigger tool. Setting: 25 hospitals across the UK, including secondary, tertiary and quaternary paediatric centres. Participants: Randomly selected children who were admitted to hospital for longer than 24 h. Outcome measures: The primary outcome measure was the rate of harm (the percentage of children experiencing one or more AEs during a hospital admission). Secondary measures were the severity of harm and performance of triggers. Results: Data from 3992 patient admissions were reviewed across the hospitals and submitted to the trigger tool portal from February 2008 to November 2011. At least one AE was reported for 567 (14.2%) patients, with 211 (5.3%) experiencing more than one event. There were 1001 AEs identified. Where harm occurred, it was considered temporary for 923 (92.2%) AEs; however, 43 (4.3%) AEs resulted in the need for life-sustaining interventions, 18 (1.8%) AEs led to permanent harm and for 17 children (1.7% of AEs) the AE was believed to have contributed to death. Conclusions: There is a significant, measurable level of harm experienced by children admitted to hospitals in the UK. While most of this harm is temporary, some of it is serious. The UKPTT offers organisations the means to measure and examine the AEs occurring in their hospital in order to reduce harm.